Коррекция траектории движения манипуляционноного робота с учетом дололнительных измерений - Цыбулькин, Г.А. (Автоматическая сварка, 2008)
The paper deals with issues associated with ensuring the required accuracy of robot motion along paths, the spatial position of which is not known exactly beforehand. The law of corrective control has been formulated, which is based on utilization of additional measurements during the motion, and which guarantees the preset movement accuracy.
Modeling of the dynamics of a system realizing this law has been performed. Выведен закон корректирующего управления, обеспечивающий движение роботов по желаемой траектории независимо от ее формы и расположения в рабочем пространстве робота, и выполнено моделирование динамики системы, реализующей этот закон коррекции.